Preliminary Study on the Expression and the Clinical Significance of CD133 in Peripheral Blood of Patients with Gastric Adenocarcinoma. (6th February 2014) - Wu, Ju-gang; Yu, Ji-wei; Lu, Rui-qi; Wang, Shou-lian; Ni, Xiao-chun; Zheng, Lin-hai; Jiang, Bo-jian
Abstract : Background . Significances of CD133 mRNA in peripheral blood mononuclear cells (PBMCs) of gastric adenocarcinoma (GC) patients were investigated. Methods . Correlations of CD133 mRNA expression in PBMCs on clinicopathological parameters or CD133 protein expression were analyzed. Receiver operating characteristic curve according to bright scale value (BSV) of CD133 mRNA was used to group patients for prognosis analysis. Results . BSV of preoperative CD133 mRNA in PBMCs in GC was significantly higher than that in volunteers or in GU. Invasive depth or metastatic lymph node number for higher BSV of preoperative CD133 mRNA and invasive depth or lymphatic vessel invasion for higher BSV of postoperative CD133 mRNA in the PBMCs were identified. Patients with CD133 + expression in primary lesion had a significantly higher expression of preoperative CD133 mRNA in the PBMCs. The expression of preoperative or postoperative CD133 mRNA in PBMCs related positively to CD133 mRNA expression in primary lesion. Patients with higher expression of preoperative or postoperative CD133 mRNA shared significantly shorter survival compared with that in lower expression group. Conclusion. Higher levels of preoperative or postoperative CD133 mRNA in PBMCs of GC correlated positively to the lymphatic metastasis and the BSV of CD133 mRNA in primary lesion, indicating the poorer survival.